East Java Local Wisdom Preservation Efforts through Extracurricular Activities in Elementary Schools - Rachmadyanti, Putri (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
Elementary school students' knowledge of local culture is decreasing, even though the importance of preserving local culture is one of the important components to be taught from an early age. One strategy to preserve local wisdom is to integrate it in extracurricular activities at school. The purpose of this study is to describe the efforts to preserve local wisdom carried out in elementary schools through extracurricular activities. The research method used is qualitative with a literature review type using the Publish or Perish application. The characteristics of the literature used are research articles in national and international journals in 2015-2021, with the keywords local wisdom, east java, extracurricular, and elementary school. The findings of the study indicate that local wisdom taught in elementary schools in East Java includes traditional East Javanese dances, musical arts and handicrafts. The strategies used by teachers during extracurricular activities are in the form of direct practice, habituation and telling the meaning and history of local wisdom to students. This activity is not only to develop students' talents and interests, but also as a means of instilling good character education for elementary school students. Students who take part in extracurricular activities based on local wisdom of East Java are also expected to be social agents of preserving local wisdom in the community through art performances to promote local wisdom of East Java. The strategies used by teachers during extracurricular activities are in the form of direct practice, habituation and telling the meaning and history of local wisdom to students. This activity is not only to develop students' talents and interests, but also as a means of instilling good character education for elementary school students. Students who take part in extracurricular activities based on local wisdom of East Java are also expected to be social agents of preserving local wisdom in the community through art performances to promote local wisdom of East Java. The strategies used by teachers during extracurricular activities are in the form of direct practice, habituation and telling the meaning and history of local wisdom to students. This activity is not only to develop students' talents and interests, but also as a means of instilling good character education for elementary school students. Students who take part in extracurricular activities based on local wisdom of East Java are also expected to be social agents of preserving local wisdom in the community through art performances to promote local wisdom of East Java. but also as a means of instilling good character education for elementary school students. Students who take part in extracurricular activities based on local wisdom of East Java are also expected to be social agents of preserving local wisdom in the community through art performances to promote local wisdom of East Java. but also as a means of instilling good character education for elementary school students. Students who take part in extracurricular activities based on local wisdom of East Java are also expected to be social agents of preserving local wisdom in the community through art performances to promote local wisdom of East Java.